REALIZATION OF 650 NM FIBER-COUPLED DIODE LASERS MODULE WITH OUTPUT BEAM REDIRECTION FOR APPLICATION IN PHOTOTHERAPY AND PHOTODYNAMIC INACTIVATION OF BACTERIALS - Nguyen Thanh Phuong, Luong Huu Bac, Quan Thi Minh Nguyet, Do Thi Kim Thoa, Nguyen Ngoc Trung; Tong Quang Cong, Tran Quoc Tien (Tạp chí Khoa học, 2023)
Currently, diode lasers in the red wavelength region, especially at 650 nm, are extensively utilized in phototherapy and photodynamic inactivation of bacterials by numerous research groups in the field of lasers for biomedical application. These devices offer exceptional advantages, such as their compact size, ease of design and integration, user-friendliness, and high safety for both operators and patients. Among these, fiber-coupled diode lasers provide an efficient solution for delivering radiation from the laser chip to the desired location. However, further optimization is still required for the fabrication technological development of these devices to meet specific application needs. This includes aspects like reducing manufacturing costs, improving component usability during operation, and meeting specialized usage requirements. To develop the technology for device fabrication, addressing the aforementioned demands, we conducted research on the design, fabrication, and characterization of fiber-coupled semiconductor lasers operating at a wavelength of 650 nm. The characterization results demonstrate that the manufactured devices can operate at maximal pumping current of 100 mA and under varying temperatures from 25oC to 40oC. Additionally, a radiation output orientation module has been designed and integrated at the end of the optical fiber to meet various demands in phototherapy and photodynamic inactivation of bacterials.